Reforming tax and welfare: Social justice and recovery after the pandemic - Felix R. FitzRoy; Jim Y. Jin (Institute of Labor Economics (IZA), 2020)
Capital income subsidies, and reliance on indirect consumption taxes have created an increasingly regressive overall tax system in the UK, US and elsewhere, with proportionately much greater impact on the poor than on the rich, and welfare cuts under ten years of austerity have had the largest impact on the most vulnerable and poorest, now magnified by the Covid-19 pandemic. We show how a progressive wealth tax combined with a uniform, linear tax on all incomes and a modest basic income, with no exemptions or reliefs and no indirect taxes except excise taxes such as fuel duties, could be highly progressive overall, as well as much fairer and simpler than the present system. Such reform would render the economy much more resilient, and potentially devastating economic consequences of the pandemic could be mitigated by an emergency basic income and suspension of rental payments.
Keywords: H2; I3; 330; COVID-19; tax; welfare; policy; pandemic